Analisis Program Kuwau Padek di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Mukomuko - Devi Mustika Rani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This exploration looks at the Advancements of the Kuwau Padek Program at the Mukomuko Regime Populace and Common EnlistmentiAdministration. How to innovate the Kuwau Padek Population Administration Service ai theiOffice ofiPopulation andiCivil Registrationiiof MukomukoiRegency is the study'siproblemiformulation. Rogers' (1995) theory of innovation is as follows: 1) Realative benefits, 2). Compatibility, as well as Complexity. Theiqualitative researchimethods usediin thisistudyiwere Theioral andiwritten dataiused inithis studyiwere obtainedithroughiinterview, observation, and documentation methods. The information investigation method utilized is the information assortment stage, information buildup, show stage, and making determinations. iAccording toithe findingsiof this study, the Kuwau Padek program is being implemented successfully in Mukomukon Regency and can assist the community in an efficient and effective manner. Keywords: Role of Women, Handling Household Waste